Ovariectomy-Induced Hepatic Lipid and Cytochrome P450 Dysmetabolism Precedes Serum Dyslipidemia - Malinská, Hana; Hüttl, Martina; Miklánková, Denisa; Trnovská, Jaroslava; Zapletalová, Iveta; Poruba, Martin; Marková, Irena (International journal of molecular sciences, 2021)
Ovarian hormone deficiency leads to increased body weight, visceral adiposity, fatty liver and disorders associated with menopausal metabolic syndrome. To better understand the underlying mechanisms of these disorders in their early phases of development, we investigated the effect of ovariectomy on lipid and glucose metabolism. Compared to sham-operated controls, ovariectomized Wistar female rats markedly increased whole body and visceral adipose tissue weight (p ˂ 0.05) and exhibited insulin resistance in peripheral tissues. Severe hepatic triglyceride accumulation (p ˂ 0.001) after ovariectomy preceded changes in both serum lipids and glucose intolerance, reflecting alterations in some CYP proteins. Increased CYP2E1 (p ˂ 0.05) and decreased CYP4A (p ˂ 0.001) after ovariectomy reduced fatty acid oxidation and induced hepatic steatosis. Decreased triglyceride metabolism and secretion from the liver contributed to hepatic triglyceride accumulation in response to ovariectomy. In addition, interscapular brown adipose tissue of ovariectomized rats exhibited decreased fatty acid oxidation (p ˂ 0.01), lipogenesis (p ˂ 0.05) and lipolysis (p ˂ 0.05) despite an increase in tissue weight. The results provide evidence that impaired hepatic triglycerides and dysregulation of some CYP450 proteins may have been involved in the development of hepatic steatosis. The low metabolic activity of brown adipose tissue may have contributed to visceral adiposity as well as triglyceride accumulation during the postmenopausal period.
Keywords: Fatty Liver; játra; obezita; metabolismus lipidů; Triglycerides; Menopause; Lipid Metabolism; Insulin Resistance; poruchy metabolismu lipidů; Diet, High-Fat; Adipose Tissue, White; Intra-Abdominal Fat; Lipid Metabolism Disorders; Female; dyslipidemie; lipidy; lipogeneze; hepatic steatosis; krysa rodu Rattus; ovariectomy; zvířata; Lipogenesis; postmenopauza; lipolýza; glukosa; hmotnostní přírůstek; potkani Wistar; Postmenopause; ztučnělá játra; hnědá tuková tkáň; Cytochrome P-450 Enzyme System; triglyceridy; ženské pohlaví; nitrobřišní tuk; menopauza; Liver; Rats, Wistar; metabolic syndrome; inzulinová rezistence; Insulin; insulin resistance; ovarektomie; Glucose; Lipids; brown adipose tissue; Weight Gain; Rats; bílá tuková tkáň; dieta s vysokým obsahem tuků; Ovariectomy; Obesity; methylglyoxal; Animals; Dyslipidemias; Lipolysis; Adipose Tissue, Brown; obesity; systém (enzymů) cytochromů P-450; inzulin